Innovative Learning Using E-Modules - Mahardika Ardi Manggala; Partono Nyanasuryanadi; Heru Suherman (Journal of Education Technology Information Social Sciences and Health, 2024)
This research discusses the innovative use of e-modules in learning and the challenges in creating or developing creative and innovative e-modules. Education in the current digital era is undergoing a significant revolution with the adoption of technology as the main catalyst for change. One of the most prominent breakthroughs in this context is the use of e-modules or electronic modules as a means of learning that combines technological sophistication and modern educational methodologies. The research methodology applied in this study is a systematic literature review (SLR) to collect and analyze relevant articles. The results of the research indicate significant innovation in improving the quality of education. E-modules provide enhanced accessibility, allowing learning from various locations and flexible timing. Interactivity through multimedia elements such as videos and animations enhances the quality of learning, making it more dynamic and engaging. Furthermore, the ability of e-modules to be tailored to individual needs and support differentiated learning creates an inclusive learning environment.